Selection of Candidates for Academic Scholarships Using Analytical Hierarchy Process (Ahp) and Simple Additive Weighting (SAW) Methods at National University - Asafalex Asafalex; M Firmansyah; Muhammad Darwis; Iqnal Shalat SW (JURNAL TEKNIK INFORMATIKA, 2022)
The National University administers several scholarships for new students each year. The problem is, the University does not yet have a standard method for determining beneficiaries. They have difficulty in determining prospective scholarship recipients with the same criteria. In fact, sometimes it only relies on people's instincts, which can be subjective. The University should implement a DSS system to overcome this problem. Therefore, in this study, the AHP method is applied and used to weight the criteria and test the level of consistency so that the criteria are in accordance with the type of scholarship. In addition, the SAW method is also used for determining scholarship recipients according to the quota. The results of this study are the priority weights of the importance of each criterion, namely the average value of report cards (0.35), parents' income (0.23), certificates (0.05), affidavits of not working and receiving scholarships (0.15), year of graduation (0.11) and number of certificates (0.10). The consistency ratio value is 0.03741 indicating the weight is consistent. This study also resulted in the best ranking of candidates for academic scholarships, with a result of 0.93. The average value of the application test results using the TAM method is 80.5%.